Correction to: Holocene thinning in central Greenland controlled by the Northeast Greenland Ice Stream (Nature Communications, (2024), 15, 1, (6434), 10.1038/s41467-024-50772-5) - Tabone, Ilaria; Robinson, Alexander; Montoya, Marisa; Alvarez-Solas, Jorge (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-50772-5, published online 31 July 2024 The original version of this article contained an error in the section, ‘Secondary effects on NGRIP thinning from other parameters’ which incorrectly read ‘this agrees with flow factors recently estimated at the NEGIS from radar and ice-flow modelling, suggesting stiffer ice along the stream flow and softer at the shear margins16’ and where reference 16 was cited incorrectly. The correct version replaces this with ‘this agrees with flow factors recently estimated at the NEGIS from radar and ice-flow modelling, suggesting stiffer ice along the stream flow and softer at the shear margins45’. Reference 45 has been added to the reference list as: 45. Gerber, T. A. et al. Crystal orientation fabric anisotropy causes directional hardening of the Northeast Greenland Ice Stream. Nat. Commun. 14, 2653 (2023). The numbering of all consecutive references in the text and in the reference list has been updated accordingly. Reference 16 is cited elsewhere in the text and remains in the manuscript unchanged. This has been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2024-11-15